Doing social research - Baker, Therese L. (Boston : McGraw-Hill College, 1999)
Offers a hands-on, step-by-step approach to social research. This work includes research studies, as well as interviews with the authors of these studies, to personalize the experience of doing social research. It exposes students to a range of research methods, encouraging them to explore the rich universe of social research
Includes bibliographical references and index.
Keywords: social sciences -- research. -- Methodology; social sciences -- methodology